Легковые автомобили - Куранский Евгений (Серия наглядных словарей, 2000)
Экземпляры: ф.17 (2002) / Инвентарный номер: 35121 / Цена: 105.00 / Сис.шифр: 39.33 / Авт.знак: Л 38 / ГРНТИ: 73.31 / ББК: 39.335.52я2